Imaging of haemodialysis-associated amyloidosis with 123I-serum amyloid P component. - Nelson, SR; Hawkins, P; Richardson, S; Lavender, J; Sethi, D; Gower, P; Pugh, C; Winearls, C; Oliver, DO; Pepys, M (1991)
Long-term haemodialysis is frequently complicated by amyloid deposition in which the fibrils consist of beta 2-microglobulin. Dialysis-related amyloid disease causes extensive morbidity and has been associated with deaths in some cases. All amyloid deposits contain amyloid P component that is derived from the normal circulating protein, serum amyloid P component (SAP). We have used scintigraphic imaging after injection of 123I-labelled SAP to assess the distribution of amyloidosis in 38 patients receiving long-term haemodialysis for end-stage renal failure. There was focal localisation of tracer at all sites where histological examination confirmed amyloid deposition. Splenic uptake was seen in 12 patients, indicating splenic amyloidosis, but there was no evidence of other visceral involvement. 6 control subjects who had been dialysed for under 1.5 years showed no localisation of tracer, nor was there any uptake of 123I-labelled human serum albumin in 3 long-term dialysis patients with histologically confirmed amyloidosis and positive 123I-SAP images. Negative scans were also obtained in 5 patients who had been transplanted 0.8-2.4 years previously, despite past evidence of dialysis arthropathy (5) and histologically proven amyloidosis (4). 123I-SAP scintigraphy may be helpful as a non-invasive method for both the diagnosis and monitoring of dialysis-associated amyloidosis.